PEMBELAJARAN KETERAMPILAN BERBICARA MELALUI PENDEKATAN PENGALAMAN BERBAHASA DI SEKOLAH DASAR - Sugiarsih, Septia (MAJALAH ILMIAH PEMBELAJARAN, 2010)
Speaking skills must be controlled by the Primary School students because these skills directly were linked with all the activities learning the student in the Primary School. The success studied the student in joining the process of the activity learning in the school really was determined by their speaking capacity command. Because through the speaking activity the student could reveal the idea, the idea, or results of his thinking to the other person orally so as the other person knew the intention or the idea of the student. The student who could not speak well and truly will experience the difficulty in joining the activity learning for all the subjects. Therefore, the teacher must be able to choose some or united various methods learning that in accordance with the condition for the student and the availability of other supporting means. Moreover, the teacher might also create the new model in the implementation learning speking skills. One of the alternatives that could be carried out in learning speaking skills spoke the student the Primary School was the application of the very polite experience approach in learning speaking skills the student the Primary School.